HUBUNGAN BUDAYA ORGANISASI DENGAN KINERJA PEGAWAI DINAS PENDIDIKAN PEMUDA DAN OLAHRAGA KOTA SAWAHLUNTO - WIDIA ANINGSIH MAN (Jurnal Bahana Manajemen Pendidikan, 2018)
This research aimed to describe the employee performance, organizational culture and cultural relations organization with the performance satisfaction at Dinas Pendidikan Pemuda dan Olahraga Kota Sawahlunto. The hypothesis of the proposed research is “organizational culture is  significantly correlated with the performance of employee at Dinas Pendidikan Pemuda dan Olahraga Kota Sawahlunto”. The present research is correlational which to see organizational culture with employee performance at Dinas Pendidikan Pemuda dan Olahraga Kota Sawahlunto. The population is 69 people and samples is 61 people. Large instrument used for data collection was a questionnaire type a Likert scale that have been valid and reliabel. The techhique of data analysis is done by using the formula Product Moment Correlation and T-test. The result of the dataanalysis showed that (1) employee performance at Dinas Pendidikan Pemuda dan Olahraga Kota Sawahlunto is in the category is good (85,15%), (2) organizational culture are on the category good (89,54%), and (3) there is a significant organizational culture between leadership with employee performance with a correlation coefficient = 0,327. So it can be concluded tha organizational culture affects employee performance at Dinas Pendidikan Pemuda dan Olahraga Kota Sawahlunto.